Effectiveness of innovation and investment activities of gas transportation enterprises - Лінчевська, Н. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article focuses on developing methodological approach for evaluating the effectiveness of innovation and investment activity of gas transmission companies. The accounting of the time factor special attention is given, which allows more reasonably evaluate the present value of future cash receipts from realization of long-term innovation and investment projects.